(untitled) (Universal International Scientific Journal, 2026)
This thesis analyzes the role of terminological competence in the professional training of future doctors in the process of teaching clinical sciences. During the study, the impact of terminological competence on clinical thinking, diagnostic decision-making, and professional communication was studied. The results of the study were processed using mathematical and statistical methods, including correlation and regression analysis, and showed that terminological training increases the effectiveness of mastering clinical knowledge.